Hebb Repetition Effect and Encoding Specificity on Memory Recall Among Undergraduates - Grace O. Anderson; Nyitor A. Shenge; Emmanuel E.Uye (CV Putra Publisher, 2026)
The study tested Hebb Repetition Effect and Encoding Specificity on memory recall among undergraduates. A 3 x 3 experimental design was adopted where 24 participants were exposed to three repetition conditions (3rd, 6th trials, and control group) and three cue conditions (reinstated, extra list, and no cues) experimental conditions. Participants’ memory recall performances were measured following each tested condition. The result reveals that participants exposed to repetition after the 3rd trial (Mean = 183.25) had significantly better memory recall compared to those exposed to the 6th trial (Mean = 162.38), and less with the control group (Mean = 147.00). Furthermore, the result demonstrates reinstated cues (Mean = 165.75) marginally facilitated better memory recall than extra list cues (Mean = 163.50), and less with control group (Mean = 163.38). However, there was no significant interaction effect between Hebb Repetition and Encoding Specificity. The study concludes that Hebb Repetition and Encoding Specificity independently significantly improve memory recall among study participants. The study recommends educators and policy makers to incorporate Hebb repetition and encoding specificity in the design and implementation of instructional materials to improve learners’ performance.